2021
DOI: 10.1111/jog.15090
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behaviors and gestational diabetes mellitus: A systematic review

Abstract: Aim: Sedentary behaviors are activities that expend less energy than 1.5 metabolic equivalents, such as watching TV, sitting. We aim to systematically review the evidence to determine the association of sedentary behavior (SB) with the risk of gestational diabetes mellitus, and the associations of SB with health outcomes in pregnant women with gestational diabetes mellitus (GDM) and women at high risk of gestational diabetes mellitus. Methods: Two researchers independently performed a literature search using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(305 reference statements)
0
2
0
1
Order By: Relevance
“…Previous research, which found that overweight and obese pregnant women had an increased risk of GD, may be attributable to inhibited insulin signalling release. 46 One meta-analysis pointed out that sedentary behaviour during pregnancy is not clearly associated with GD, perhaps because of reporting differences and measuring challenges, 47 but weight gain resulting from sedentary behaviour and vascular factors is confirmed as being associated with GD. Pregnant women should reduce their sedentary time and maintain a low prepregnancy BMI to prevent and reduce the risk of GD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research, which found that overweight and obese pregnant women had an increased risk of GD, may be attributable to inhibited insulin signalling release. 46 One meta-analysis pointed out that sedentary behaviour during pregnancy is not clearly associated with GD, perhaps because of reporting differences and measuring challenges, 47 but weight gain resulting from sedentary behaviour and vascular factors is confirmed as being associated with GD. Pregnant women should reduce their sedentary time and maintain a low prepregnancy BMI to prevent and reduce the risk of GD.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies were assessed using the following items developed from the Joanna Briggs Institute critical appraisal checklists [37]: (1) study design allowed for causal inference (only for longitudinal study design); (2) random selection of study participants and/or study sites; (3) detailed description of sample characteristics; (4) valid assessment of motor competence; (5) valid assessment of executive functions; and (6) adjustment for relevant confounders in the analysis. Based on the assessment criteria, the risk bias for each included study was categorised based on the percentage of items rated as "yes" > 70% (low), 50-69% (moderate), or < 50% (high) [38,39].…”
Section: Criteria For Risk Of Bias Assessmentmentioning
confidence: 99%
“…Wu et al ( 2022) 214 observaron que la actividad física no previene la aparición de DMG, aunque sí tiene un efecto positivo en la ganancia de peso de las gestantes cuando se combina con una dieta equilibrada. Por otro lado, Li et al (2021) 215 no encontraron asociación entre la conducta sedentaria y el riesgo de DMG, aunque afirman que el sedentarismo puede modificar los resultados metabólicos durante la gestación. En el estudio actual, no se encontraron diferencias en los niveles de actividad física y sedentarismo entre las gestantes con y sin DMG.…”
Section: Asociación De Los Estilos De Vida Con Dmgunclassified